Going Private Economic Motives - Jarosław Kowalczyk; Lidia Makowiecka; Piotr Szczepankowski (Contemporary Economics)
The article presents main economic motives for going private strategies. The problem is presented from empirical point of view. We have also been interested in Polish cases of going private, which are presented in the last part of article.